Interconnections between digital business transformation and Marketing 5.0 (Research, Society and Development, 2022)
The fourth industrial revolution has provided the digital transformation, even influencing business and marketing. Based on this, this article presents possible interconnections between the digital transformation of businesses and Marketing 5.0. To meet this objective, a comparative analysis was carried out between a set of domains of digital business transformation and the components of Marketing 5.0. This is a qualitative and exploratory theoretical essay based on bibliographical research that involves comparative analysis between the themes in question. As a result, points of convergence were identified between the subjects under study, having as possible points of interconnection the use of digital technologies in interacting with consumers, making business decisions based on data, agility in trying out strategies and in innovation. With the study carried out, it was also verified the importance of developing a digital culture and analytical maturity both in the process of digital business transformation and in the adoption of Marketing 5.0.